Junior Leadership Program: Empowering Elementary Students to Develop 4C Skills (Critical Thinking, Creativity, Communication, Collaboration) - MY, Nurfadila (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: The Junior Leadership Program aims to enhance 4C skills—Critical Thinking, Creativity, Communication, and Collaboration—among elementary students, addressing the critical gap in traditional education that prioritizes rote learning over essential skills development. Research Design and Methodology: Conducted at SDI BTN IKIP 1 in Makassar, this study involved 20 students (15 girls and 5 boys) employing Participatory Action Research (PAR) to integrate 4C skills into the curriculum. Data were collected through surveys, interviews, and SWOT analysis. Implementation included workshops, focus group discussions, and project-based learning activities. Findings and Discussion: Findings indicate significant improvements in students' analytical and creative problem-solving abilities, communication skills, and teamwork. Teachers reported increased proficiency in integrating 4C skills, while parents observed enhanced confidence and problem-solving capabilities in their children. Challenges such as aligning new curricula with existing standards and securing consistent parental engagement were mitigated through targeted teacher training and parental workshops. Implications: These findings underscore the need for educational reforms incorporating 4C skills and suggest that similar programs could be adapted to diverse educational contexts. Future research should explore the long-term impacts and strategies for broader implementation of 4C skill development in elementary education.